Variations in Vertical CO/CO2 Profiles in the Martian Mesosphere and Lower Thermosphere Measured by the ExoMars TGO/NOMAD: Implications of Variations in Eddy Diffusion Coefficient. Issue 10 (25th May 2022) - Yoshida, Nao; Nakagawa, Hiromu; Aoki, Shohei; Erwin, Justin; Vandaele, Ann Carine; Daerden, Frank; Thomas, Ian; Trompet, Loïc; Koyama, Shungo; Terada, Naoki; Neary, Lori; Murata, Isao; et al.
Abstract: Using the Nadir and Occultation for MArs Discovery instrument aboard Trace Gas Orbiter, we derived the CO/CO2 profiles between 75 and 105 km altitude with the equivalent width technique. The derived CO/CO2 profiles showed significant seasonal variations in the southern hemisphere with decreases near perihelion and increases near aphelion. The estimation of the CO/CO2 profiles with a one‐dimensional photochemical model shows that an altitude‐dependent eddy diffusion coefficient better reproduces the observed profiles than a vertically uniform one. Our estimation suggests that the eddy diffusion coefficient in L s = 240–270 is uniformly larger by a factor of ∼2 than that in L s = 90–120 in the southern hemisphere, while they are comparable in the northern hemisphere. This fact demonstrates that the eddy diffusion coefficient is variable with season and latitude. Plain Language Summary: The eddy diffusion coefficient is widely used to parameterize the efficiency of vertical diffusion in the planetary atmosphere, whose variation characterizes the transportation of trace gas species. Additionally, it could vary their vertical distributions in the middle and upper atmosphere, which might cause an impact on the species escaping to space. However, the variability of the eddy diffusion coefficient in those altitude regions have been poorly understood. In this study, we focus on the estimation of variation in the eddy diffusion coefficient by analyzing the CO and CO2 measurements made by the ExoMars Trace Gas Orbiter. The observed CO/CO2 ratio between altitudes of 75 and 105 km shows a significant seasonal variation in the southern hemisphere. The observed CO/CO2 profiles are compared with the simulated profiles obtained with a one‐dimensional photochemical model assigning several shapes and intensity of eddy diffusion coefficient. The comparison shows that the eddy diffusion coefficient is not constant but variable depending on altitude, season, and latitude, which suggests that the efficiency of the vertical diffusion varies with season and latitude. This fact is useful to other 1D photochemical models to reproduce the seasonal and latitudinal variation of atmospheric composition. Key Points: The CO/CO2 profiles from 75 to 105 km measured by NOMAD aboard TGO are used to investigate variations in the eddy diffusion coefficient The estimated CO/CO2 profiles agree well with the observed profiles if altitude‐dependent eddy diffusion coefficients are considered Our results demonstrate a substantial seasonal variation in the eddy diffusion coefficient in the southern hemisphere